Drug–drug interaction between valproic acid and meropenem: a retrospective analysis of electronic medical records from neurosurgery inpatients. (1st February 2017) - Wen, Z.‐P.; Fan, S.‐S.; Du, C.; Yin, T.; Zhou, B.‐T.; Peng, Z.‐F.; Xie, Y.‐Y.; Zhang, W.; Chen, Y.; Xiao, J.; Chen, X.‐P.
Summary: What is known and objective: A series of studies have indicated that valproic acid (VPA) plasma concentration decreased rapidly when used concomitantly with carbapenem antibiotics, including meropenem (MEPM), imipenem and panipenem, which may increase the risk of seizure breakthrough. However, the cause for the change in VPA pharmacokinetics is unclear. A retrospective analysis of VPA therapeutic drug monitoring (TDM) records was performed to investigate this VPA pharmacokinetics drug–drug interaction. Methods: Three hundred and eighty one VPA TDM records from the Department of Neurosurgery of Xiangya Hospital from January 2012 to December 2014 were collected. The VPA TDM records were categorized by VPA and MEPM daily dosages in grams/day (g/day). A comparison of VPA plasma levels among different groups was performed to investigate the change in VPA level in this drug interaction. Results and discussion: Remarkable decreases in VPA plasma level were observed when the drug was used concomitantly with MEPM in both 1.2 g/d and 1.6 g/d VPA groups (67·3 ± 4·6 μ g/mL, n = 21 vs. 15·3 ± 1·9 μ g/mL, n = 15, P < 0·001; 67·6 ± 1·2 μ g/mL vs. 18·1 ± 2·6 μ g/mL, n = 38, P < 0·001). No significant difference in VPA plasma concentrations was observed between the 1·2 g/day VPA + MEPM, 1·6 g/day VPA + MEPM and 2·0 g/day VPA + MEPM groups (15·3 ± 1·9 μ g/mL, n = 15 vs. 18·1 ± 2·6 μ g/mL, n = 38 vs. 9·0 ± 3·0 μ g/mL, n = 7; P = 0·252). The decrease in VPA concentration was independent of MEPM daily dose (14·0 ± 5·1 μ g/mL, n = 4 for high MEPM daily dose vs. 16·5 ± 1·9 μ g/mL, n = 56 for low MEPM daily dose; P = 0·729). After discontinuation of MEPM for more than 7 days, VPA plasma concentration recovered to a value comparable to that before MPEM initiation (69·7 ± 4·2 μ g/mL, n = 21 vs. 51·2 ± 8·1 μ g/mL, n = 9; P = 0·48). What is new and conclusion: This is the first study using a large number of VPA TDM records to investigate the change in VPA levels caused by concomitant use of MEPM. Our results imply that the decrease in drug concentration cannot be reversed by increasing VPA dose. Moreover, MEPM daily dose did not influence the drop in VPA plasma level. At least 7 days are required for the recovery of VPA plasma concentration after discontinuation of MEPM. Abstract : The magnitude of decrease in VPA plasma concentration was independent of VPA and MEPM daily dose in this drug‐drug interaction.